2018
DOI: 10.7717/peerj.5103
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic evidence for involvement of reactive oxygen species in Rhizoctonia solani AG1 IA sclerotia maturation

Abstract: Rhizoctonia solani AG1 IA is a soil-borne fungal phytopathogen that can significantly harm crops resulting in economic loss. This species overwinters in grass roots and diseased plants, and produces sclerotia that infect future crops. R. solani AG1 IA does not produce spores; therefore, understanding the molecular mechanism of sclerotia formation is important for crop disease control. To identify the genes involved in this process for the development of disease control targets, the transcriptomes of this speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 49 publications
0
10
0
2
Order By: Relevance
“…In this study, we performed RNAseq analysis of a highly virulent strain of R. solani, Wgl-2 to identify the repertoire of expressed genes in a pectin-based growth medium. In earlier studies, serious attempts have been made to generate the transcriptome data of R. solani AG1 IA from China (Zheng et al 2013;Zhu et al 2016;Copley et al 2017;Liu et al 2018). In a recent report, transcriptome analysis of an Indian strain BRS1 was performed to identify the pathogenicity determinants of R. solani during infection process in rice and the study suggested that functional validation of identified genes would be crucial to get insights about this important pathosystem and to manage this devastating disease (Ghosh et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we performed RNAseq analysis of a highly virulent strain of R. solani, Wgl-2 to identify the repertoire of expressed genes in a pectin-based growth medium. In earlier studies, serious attempts have been made to generate the transcriptome data of R. solani AG1 IA from China (Zheng et al 2013;Zhu et al 2016;Copley et al 2017;Liu et al 2018). In a recent report, transcriptome analysis of an Indian strain BRS1 was performed to identify the pathogenicity determinants of R. solani during infection process in rice and the study suggested that functional validation of identified genes would be crucial to get insights about this important pathosystem and to manage this devastating disease (Ghosh et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For example, antioxidant molecules such as glutathione or thioredoxin would reduce target proteins through their dithiol/disulphide groups, and these processes are catalysed by a group of enzymes including glutathione S-transferase, glutathione peroxidase and thioredoxin to detoxify the oxidative stress of ROS [21,107]. Therefore, genes encoding these enzymes may be important for regulating the cellular redox state during sclerotia initiation, and studies have shown that glutathione S-transferase and glutathione peroxidase were up-regulated during sclerotia formation in R. solani [28,30]. The thioredoxin reductase gene-silenced mutant SsTrr1 of S. sclerotiorum ws also shown to decrease sclerotia numbers [108].…”
Section: Gene Functions Associated With Sclerotia Numbermentioning
confidence: 99%
“…When plants are infected by pathogens and viruses, a large amount of ROS will burst at the attack sites. ROS is an oxygen-containing group with higher oxidation activity or partial reduction than oxygen. , It mainly includes superoxide anion radicals, hydrogen peroxide (H 2 O 2 ), hydroxyl radicals, and singlet oxygen. , At present, many studies have shown that ROS will burst when plants, such as rice, potatoes, soybeans, beans, tomatoes, carrots, and tobacco are infected with pathogens . For example, ROS burst happens after rice inoculation with Rhizoctonia solani ( R. solani ) or Magnaporthe grisea . Pesticides are released under the stimulation of ROS to achieve rapid and targeted release responding to areas with diseases. , A ROS-responsive release system can overcome the disadvantages of environmental response. A typical method is to use ROS cleavable groups as a carrier to prepare a slow-release system. , These materials are cheap and safe but have not been used in agriculture.…”
Section: Introductionmentioning
confidence: 99%